Greenhouse gas emissions are affected by land use type in two agroforestry systems: Results from an incubation experiment. Issue 6 (14th August 2020) - Li, Ping; Lang, Man; Zhu, Sixi; Bork, Edward W.; Carlyle, Cameron N.; Chang, Scott X.
Abstract: In order to better understand factors affecting greenhouse gas (GHG) emissions in Canadian agroforestry systems, we conducted a laboratory incubation study to assess N2 O, CO2 and CH4 emissions from soils in response to land use (forestland vs. cropland) and agroforestry system type (hedgerow vs. shelterbelt) in central Alberta, Canada. Emissions of N2 O were lower in soils from forestland than cropland, and forest soils acted as a net sink of atmospheric CH4 while cropland soils were weak sources of CH4 . However, the forest soil had higher CO2 emission rates than the cropland soil within both agroforestry systems. Soil CH4 oxidation was higher in soil from hedgerow (consisted of natural forest vegetation) than from shelterbelt system (planted forest vegetation), while the former also had lower N2 O emissions. Overall, soil CO2 emissions were significantly higher from hedgerow than from shelterbelt systems. Emissions of N2 O were positively related with gross nitrification rates and soil pH, and negatively related with gross N immobilization rates. The CO2 emissions were positively related with water‐soluble organic C contents, while CH4 emissions were positively related with clay content, but negatively with gross N immobilization rates and soil organic C content. The global warming potential was higher in forestland soil than in cropland soil within agroforestry systems, and higher in forestland soil of the hedgerow compared to that in shelterbelts. Our results suggest that we need to select land uses or agroforestry systems that have a higher potential of mitigating GHG emissions from soils. Abstract : This study assessed the N2 O, CO2 and CH4 emissions from soils in response to land use (forestland vs. cropland) and agroforestry system type (hedgerow vs. shelterbelt) through a laboratory incubation experiment. We found that the global warming potential was higher in forestland soil than in cropland soil within agroforestry systems, and higher in forestland soil of the hedgerow compared to that in shelterbelts. Our results suggest that we need to select land uses or agroforestry systems that have a higher potential of mitigating GHG emissions from soils.